(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
The article analyzes the deep significance of the criteria of authenticity in the framework of pedagogical measures in the assessment of reading comprehension skills, as well as the evaluation of these criteria. In addition, the article provides an analysis of the changes that occur in the education system, people’s minds and the society in which they live as a result of the test’s washback. It reveals some necessary principles that form in the curriculum and teaching methods which take place as a consequences of washback effect of language tests.